La inteligencia artificial y su impacto en el comportamiento social: una revisión de alcance - Franyelit Suarez (Corporación Universitaria Minuto de Dios, 2023)
This paper presents a documentary review of the challenges of artificial intelligence in today's world and the social challenges of coexisting with new technologies. For this purpose, a literature search was carried out in the leading open-access journals. In addition, a simple random population was surveyed using artificial intelligence and the possible impacts on social behavior. The results show that the literature aligns with the social perception that the excessive use of intelligent tools can be detrimental to people and that it is essential to be cautious with intelligent applications.